The Relevance of Social Reconstruction Curriculum in the 2013 Curriculum on Arabic Learning/ ملائمة المنهج إعادة الإعمار الاجتماعي في المناهج الدراسي 2013 في تعليم اللغة العربية - Muhimmatul Choiroh; Muhammad Nashrullah (Journal of Arabic Language Studies and Teaching, 2021)
ABSTRACT The educational curriculum will not be separated from the basic principles or foundations. In this case, the study that will be raised is within the scope of the relevance of the social reconstruction curriculum with the Problem Based Learning (PBL) model in the 2013 curriculum on Arabic language learning. This research uses a type of evaluative method with a qualitative approach. The goal is to find out the relevance of the curriculum to the public model in Arabic language teaching. As for the results of the research, the relevance of the social reconstruction curriculum by using problem-based learning models can be said to be relevant, because it is in accordance with the plan of implementation of Arabic language learning with evidence that the steps in the RPP are in accordance with the stages of PBL learning.